Love me, love me not: A nuanced view on collaboration in sustainable supply chains. Issue 3 (September 2015) - Touboulic, Anne; Walker, Helen
Abstract In this paper we investigate the collaborative paradigm in Sustainable Supply Chain Management (SSCM). The depth and quality of the relationship between a firm and its suppliers is widely recognised as a critical facilitator of SSCM. Many authors in the field have argued that a collaborative approach to SC relationship management was likely to be more fruitful in achieving sustainable development goals. However, little research has offered a more nuanced perspective on collaborative SSCM and specifically assessed its feasibility outside the context of large companies collaborating on environmental activities. In this paper, we explore collaboration in SSCs through a qualitative study of a large multinational in the food sector working with small agricultural suppliers. We show that there are both supporting and hindering factors to collaborative SSCM. The study reveals the dynamic nature of SC relationships for sustainability and that collaboration can be developed through time thanks to investment in both formal relationship building mechanisms and more relational aspects. The main contributions of the paper lie in its nuanced view of collaboration for SSCM and systematic application of relational theory (Dyer and Singh, 1998) in SSCM.